Implications of non-utilization of population data For development planning in Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The paper examines implications of non-utilization of population data for development planning in Nigeria. In developing countries, including Nigeria, population data are not adequately used for development planning. Whilst in developed countries of the worldpopulation data constitute an indispensable element of planning and development. Using Social development theory as a framework. This paper identified implications of nonutilization of population data and how this affect development planning in Nigeria. Data for the paper were obtained through the secondary sources like the Nation Bureau of Statistics, National Population Commission and academic journals. The findings show that the slow level of development in Nigeria is as a result of non-use of population data. The study also showsthat planning in Nigeria is ineffective because population data are underutilized. Therefore, the paper recommends that there is need for effective utilization of population data by the government, development partners and private sectors for effective planning. This couldfacilitate greater pull of economic and social development of any nation. Interactions of population experts with government improves the integrity of systems and increase administrative efficiency of any nation of the world towards the use of population data that willstimulus development and economic planning.
Keywords: Population; Data; Census; Development Planning; Vital Statistics